Optimalisasi Perawatan Sistem Pendingin Mesin Utama Tipe Hansin GLU28AG Pada Kapal - Joko Subekti; Waris Wibowo; Ningrum Astriawati; Muhammad Hamzah Fadholy (Dinamika Bahari, 2022)
The cooling system on the diesel engine is the main engine cooling system of the Hansin GLU28AG type on the KM Ship. Abadi Sejahtera is a closed cooling system using 2 media, namely freshwater media and seawater media. Maintenance according to the manual book serves to keep the cooling system working optimally. The purpose of this study is to find out the steps to optimize the maintenance of the main engine cooling system of the Hansin GLU28AG type on KM Ships. Abadi Sejahtera. This research was carried out in the engine room of the KM Ship. Abadi Sejahtera. The method used in this research is a qualitative descriptive approach. The data collection methods used are documentary methods, interview methods, and observation methods. From the results of the study showed the maintenance carried out in the cooling system of the main engine type Hansin GLU28AG on km ships. Abadi Sejahtera runs optimally. The average result after optimization of treatment by 90%. The implementation of maintenance on diesel engine cooling system components includes expansion tanks, fresh water pumps, fresh water coolers, sea chests.